Military Expenditure Economic Growth Nexus in Jordan: An Application of ARDL Bound Test Analysis in the Presence of Breaks. Issue 7 (3rd October 2021) - Dimitraki, Ourania; Win, Sandar
ABSTRACT: The Hashemite Kingdom of Jordan is a nation that has persisted through turbulent times. The country's leaders have long attempted to balance the allocation of resources between a strong military and a developing economy in their quest for stability, peace and prosperity. This paper examines and sheds further light on the relationship between Jordan's military expenditure and its economic growth during the period 1970–2015. Using the Gregory -Hansen cointegration technique allowing for structural breaks, and the ARDL methodology this paper tests the short – and long–run equilibrium relationship between military expenditure and economic growth in Jordan. Furthermore, with the error correction model (ECM) and the CUSUM and CUSUMSQ tests, we examine the stability of the above relationship. The results reveal positive short – and long–run relationships between military expenditure and economic growth in Jordan, during the period under study. This finding has important policy implications for the Jordanian state, as it justifies the transfer of resources to the military, showing that it has not had a negative impact on economic growth.